2012
DOI: 10.1182/blood-2011-11-392167
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy is required for CSF-1–induced macrophagic differentiation and acquisition of phagocytic functions

Abstract: Autophagy is the process by which superfluous or damaged macromolecules or organelles are degraded by the lysosome. Pharmacologic and genetic evidence indicates that autophagy plays pleiotropic functions in cellular homeostasis, development, survival, and differentiation. The differentiation of human blood monocytes into macrophages is a caspase-dependent process when triggered ex vivo by colony stimulating factor-1. We show here, using pharmacologic inhibitors, siRNA approaches, and Atg7 ؊/؊ mice, that autoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
128
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(135 citation statements)
references
References 20 publications
4
128
2
1
Order By: Relevance
“…More recently we established that the induction of autophagy is also a prerequisite for CSF1-induced monocyte differentiation and the acquisition of phagocytic functions. 7,8 In the same line, it has been previously reported that induction of autophagy is essential for monocyte-macrophage differentiation upon CSF2/GM-CSF stimulation. Indeed, CSF2 induced MAPK8/JNK1 activation to mediate the induction of autophagy and monocyte survival.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…More recently we established that the induction of autophagy is also a prerequisite for CSF1-induced monocyte differentiation and the acquisition of phagocytic functions. 7,8 In the same line, it has been previously reported that induction of autophagy is essential for monocyte-macrophage differentiation upon CSF2/GM-CSF stimulation. Indeed, CSF2 induced MAPK8/JNK1 activation to mediate the induction of autophagy and monocyte survival.…”
Section: Discussionsupporting
confidence: 57%
“…[26][27][28] Notably, the differentiation of hematopoietic cells requires intense energy consumption, membrane remodeling and/or organelles elimination, as exemplified for myeloid, megakaryocytic, or erythroid differentiation. 7,11,29,30 Physiological monocyte differentiation triggered by CSF1R engagement requires the formation of a multimolecular complex consisting of FADD, CFLAR/FLIP, CASP8, RIPK1 and other protein partners; and CASP8 acts as the initiatory caspase to induce the cleavage of key protein substrates (such as RIPK1 and NUCLEOPHOSMIN, among others) that orchestrate the differentiation process. 6,31 Accordingly, inhibition of caspase activation with pancaspase inhibitors or by CASP8 silencing is sufficient to dampen the differentiation of human monocytes into macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When monocytes are stimulated to differentiate into macrophages, autophagy is induced via increased expression and phosphorylation of ULK1. 37,38 Studies involving the inhibition of autophagy by pharmacological agents, siRNA approaches or Atg7 knockout mice show that the CSF1-driven differentiation of monocytes into macrophages is significantly hampered ( Table 1). 37,38 CSF2/GM-CSF (colony-stimulating factor 2 [granulocyte-macrophage]) is another important factor that can drive the differentiation of monocytes into macrophages, and it was demonstrated that autophagy is induced during monocyte differentiation into macrophages triggered by CSF2 in vitro and by thioglycolate in vivo.…”
mentioning
confidence: 99%
“…18 Therefore, we propose that the effect of M-CSF on chemoresistance is possibly mediated by autophagy and apoptosis. In this study, we found that cytoplasmic M-CSF-induced doxorubicin (Adriamycin, ADM) resistance is mediated by apoptosis inhibition through activation of the PI3K/Akt/Survivin pathway in MCF-7 cells.…”
Section: Introductionmentioning
confidence: 99%